Ewolucyjny rozwój rachunkowości — zarys problemu - Ćwiąkała-Małys, Anna; Karpińska, Marzena (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
Despite possible assumptions, accountancy is not a new phenomenon in economy, it has a very rich tradition, whose development has been shaped by many global events. The earliest evidence of accountancy was known in the Antiquity, but the first instances of double-entry book-keeping come from Northern Italy and date back to the 14th century. The conditions of accountancy development: emergence of a new numeric system, trade with the East, invention of printing and the location where all this took place suggest extraordinary cosmopolitanism of our forefathers. Political tremors, epidemics, stagnation periods and huge growth in industry, as well as the people with their drive towards learning and wealth, were also significant for accountancy. Accountancy has become more important over time, giving rise to such new professions as an accountant or an audit expert and creating many organisations for research promotion and support as well as rules and standards, some of which serve both the theoreticians and practitioners of accountancy to this day.
Keywords: rachunkowość; historia